DEVELOPING INSTRUCTIONAL READING MATERIALS WITH LOCAL CULTURE-BASED NARRATIVE TEXTS FOR THE TENTH GRADE STUDENTS - Rita Inderawati; Sri Susanti; Nurhayati Nurhayati; Margaretha Dinar Sitinjak (English Review: Journal of English Education, 2022)
The purposes of this study was to find out the validity, practicality, and potential effect of the developed instructional reading materials using Siti Zubaidah narrative lyrics as a local culture-based narrative texts from South Sumatra. The method of the research used development study. The subjects of the study were tenth grade students whose instructional reading level was level four. The procedure of the study consisted of three stages: analysis, design, evaluation and revision. In the first stage, instructional, students’ reading level, and their reading needs were analyzed. The data collected by using questionnaire and test. The result of the analyses became the basis of product development. Texts with comprehension questions were written. Formative evaluation was conducted to see the validity, practicality, and potential effects of the product. The validity about the content and construct of the product was evaluated in expert review phase. The product was stated to be very highly valid (4.45). The practicality was evaluated in one-to-one and small group phases. The results showed that the product was very highly practical since the average score in both phases were 4.64 and 4.79 respectively. Field test phase aimed to evaluate the potential effect of the product. After being tried-out in the field test as 93.3% of the students achieved the minimum mastery criterion which was 68. It meant that this product had a very high potential effect. In conclusion, the developed product was potentially effective to be applied for the tenth grade students.